2020
DOI: 10.33093/ijoras.2020.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Development of Visual-based Rehabilitation Using Sensors for Stroke Patient

Abstract: This project concerns on the development of applications using sensors for the rehabilitation of stroke patients. Thus, the leap motion sensor is employed for the finger motor rehabilitation training while the Microsoft Kinect sensor is utilized for the upper limb motor rehabilitation. Two applications which are named ‘Pick and Place’ and ‘Stone Breaker’ are developed. For the first application, the patient is required to pick up the virtual blocks and stack it up. The ‘Stone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Effort expectancy is the level of comfort with regards to using a system [2]. Researchers Too and Chang [1], Abbad [13], Dönmez-Turan and Kir [17] and Chen and Huang [18] in their individual studies confirmed that users' effort expectancy determined their behavioral intentions.…”
Section: ) Utautmentioning
confidence: 88%
See 1 more Smart Citation
“…Effort expectancy is the level of comfort with regards to using a system [2]. Researchers Too and Chang [1], Abbad [13], Dönmez-Turan and Kir [17] and Chen and Huang [18] in their individual studies confirmed that users' effort expectancy determined their behavioral intentions.…”
Section: ) Utautmentioning
confidence: 88%
“…Interactive technology like Kinect, can act as a natural user interface (NUI). Many studies have benefited from Kinect [1], [2], [3], [4], such that Kinect would be applicable in education field; in this case, for any school children whose learning methods are not accustomed for in the existing learning situation in Malaysia. In minimizing these gaps found in the current Malaysian education system, a conceptual framework utilizing Microsoft Kinect is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to display a virtual object to the marker (such as a QR code or 2D image) in the real world through the camera, a Vuforia engine is needed. It is an software development kit (SDK) for smartphone that can help determine which marker is suitable to display virtual objects and track planar images in realtime [18].…”
Section: B Unity and Vuforiamentioning
confidence: 99%
“…Additionally, the battery can be recharged through a solar panel. Sonar sensors are deployed for obstacle detection along the robot's path [18].…”
Section: Sherly Stalin Et Al Introduced An Innovative Grass Cutter In...mentioning
confidence: 99%